Impacts of the EU's Common Agricultural Policy “Greening” reform on agricultural development, biodiversity, and ecosystem services - Jordan Hristov; Yann Clough; Ullrika Sahlin; Henrik G. Smith; Martin Stjernman; Ola Olsson; Amanda Sahrbacher; Mark V. Brady (Applied Economic Perspectives and Policy, 2020)
The EU's Common Agricultural Policy (CAP) has had limited success in mitigating agriculture's environmental degradation. In this paper we simulate the impacts of the 2013 “greening” reform on biodiversity and ecosystem services in environmentally contrasting landscapes. We do this by integrating an agent-based model of structural change with spatial ecological production functions, and show that the reform will likely fail to deliver substantial environmental benefits. Our study implies that greening measures need to be tailored to local conditions and priorities, to generate environmental improvements. Such spatial targeting of measures is though incompatible with the design of a common direct payments scheme.
Keywords: 630; agent-based modeling; biodiversity; CAP reform; Ecological Focus Areas (EFA); ecosystem services; landscape; spatial production functions